Stimulation of TLR4 by recombinant HSP70 requires structural integrity of the HSP70 protein itself - Luong Michael; Zhang Yanyu; Chamberlain Tim; Zhou Tianhui; Wright Jill F; Dower Ken; Hall J Perry (BMC, 2012)
Abstract Background Toll-like receptor 4 (TLR4) is activated by bacterial endotoxin, a prototypical pathogen-associated molecular pattern (PAMP). It has been suggested that TLR4 can also be activated by damage-associated molecular pattern (DAMP) proteins such as HSP70. It remains a challenge to provide unequivocal evidence that DAMP proteins themselves play a role in TLR4 activation, as the DAMP proteins used are often contaminated with endotoxin and other TLR ligands introduced during protein expression and/or purification. Results Here we report that the activation of TLR4 on primary human macrophage cultures by recombinant HSP70 is not solely due to contaminating endotoxin. Polymyxin B pretreatment of HSP70 preparations to neutralize contaminating endotoxin caused significant reductions in the amount of TNF-α induced by the recombinant protein as determined by ELISA. However, digestion of HSP70 with Proteinase K-agarose beads also dramatically reduced the TNF-α response of macrophages to HSP70, while leaving levels of contaminating endotoxin largely unchanged relative to controls. Conclusions These results indicate that the stimulatory effect of recombinant HSP70 requires both the presence of endotoxin and structural integrity of the heat shock protein itself.